2014
DOI: 10.1074/jbc.m114.577353
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Nsp10, a Critical Co-factor for Activation of Multiple Replicative Enzymes

Abstract: Background: SARS-CoV nsp10 binds and stimulates both the nsp14 and nsp16 activities. Results: We mapped the nsp10 surface interacting with nsp14 and demonstrated that this surface plays a critical role in SARS-CoV replication. Conclusion:The core interaction domain of nsp10 is essential for SARS-CoV replication. Significance: This nsp10 core represents an attractive target for antiviral drug development against various pathogenic coronaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
238
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 66 publications
13
238
0
1
Order By: Relevance
“…The involvement of nsp10 in coronavirus RNA synthesis was first reported from the analysis of MHV mutants (153). More recently, it has been shown that nsp10 acts as a cofactor of both nsp14 ExoN and nsp16 methyltransferase (MTase) activities (154). Moreover, as nsp14 and nsp16 bind to overlapping nsp10 sites, nsp10 might act as a molecular switch, mediating interactions between RNA and proteins from both proofreading and mRNA capping machineries.…”
Section: Cellular and Viral Proteins Of The Coronavirus Replication-tmentioning
confidence: 99%
“…The involvement of nsp10 in coronavirus RNA synthesis was first reported from the analysis of MHV mutants (153). More recently, it has been shown that nsp10 acts as a cofactor of both nsp14 ExoN and nsp16 methyltransferase (MTase) activities (154). Moreover, as nsp14 and nsp16 bind to overlapping nsp10 sites, nsp10 might act as a molecular switch, mediating interactions between RNA and proteins from both proofreading and mRNA capping machineries.…”
Section: Cellular and Viral Proteins Of The Coronavirus Replication-tmentioning
confidence: 99%
“…There are multiple interactions between the individual replicase gene-encoded nsps and the structural basis and functional implications of these interactions have been studied in a few cases. For example, it has been shown that the exoribonuclease and ribose 2 O-methyltransferase activities associated with nsp14 and nsp16, respectively, are each stimulated by specific interactions with nsp10 (Bouvet et al, 2014;Decroly et al, 2011). Also, there is evidence that a heteromultimeric complex formed by nsp7 and nsp8 interacts with (and serves as a processivity factor for) the RNA-dependent RNA polymerase (RdRp, nsp12) (Zhai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is evidence that a heteromultimeric complex formed by nsp7 and nsp8 interacts with (and serves as a processivity factor for) the RNA-dependent RNA polymerase (RdRp, nsp12) (Zhai et al, 2005). Additional interactions between individual subunits of the RTC have been suggested on the basis of two-hybrid screening data (Pan et al, 2008;von Brunn et al, 2007) and there is evidence that a substantial number of coronavirus nsps form homo-and/or heterooligomeric complexes (Anand et al, 2002(Anand et al, , 2003Bouvet et al, 2014;Chen et al, 2011;Ricagno et al, 2006;Su et al, 2006;Xiao et al, 2012;Zhai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Mpro domain was encoded between TM2 and TM3, a location conserved in all nidoviruses. We also identified a homologue of coronavirus non-structural protein 10 (nsp10), a zinc-binding protein that is involved in RNA synthesis (Bouvet et al, 2014).…”
mentioning
confidence: 99%